Impact of thermally modified wood on mechanical properties of mortar. (30th May 2019) - Guo, Aofei; Aamiri, Osama Bu; Satyavolu, Jagannadh; Sun, Zhihui
Highlights: The effects of partially replacing sand with ground wood chips on mortar were investigated. The impacts of torrefaction treatment on wood chips were discussed. The properties of mortar with highly or lightly torrefied wood chips were compared. The interfacial bonding between wood chips and cement matrix was evaluated. Abstract: In this study, the impact of partially replacing sand with sustainable and renewable biomass such as ground wood chips on the mechanical properties of mortar is investigated. The effect of thermal treated biomass on strength properties is also studied. Compared to the mortar containing untreated ground wood chips, those containing highly or lightly torrefied ground wood chips were found to have higher flexural strength and compressive strength due to the enhanced bonding between the wood chips and paste matrix. Although all the tested mortars with ground wood chips have lower strength than the mortar without any wood chips, their flexural toughness and toughness indices were found to be comparable or higher than the controlled mortar, indicating better energy absorption capacity and post-peak behavior.